Preliminary Analysis of Assessment Instrument Design to Reveal Science Generic Skill and Chemistry Literacy - Woro Sumarni; Sudarmin Sudarmin; Wiyanto Wiyanto; Supartono Supartono (International Journal of Evaluation and Research in Education (IJERE), 2016)
The purpose of this research is to design assessment instrument to evaluate science generic skill (SGS) achievement and chemistry literacy in ethnoscience-integrated chemistry learning. The steps of tool designing refers to Plomp models including 1) Investigation Phase (Prelimenary Investigation); 2) Designing Phase (Design);  3) Construction/Realization Phase (Realization/Construction) ; 4) Test, Evaluation and Revision Phase. (Test, Evaluation and Revision).  To test the validity of assessment instrument, it was used content validity by three experts as validators, while to test the practical, it was used questionnaire which were given to 22 college students of food ingredients chemistry that is integrated of ethno-science and two supporting lecturers. The result of content validity showed that assessment tool which was developed was valid stated by experts with the reliability coefficient was 0,72. Every lecturers and 21 students gave positive response, so it can be concluded that developed assessment instrument was practice to use.